1974
DOI: 10.1021/bi00707a005
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and pH dependence of ficin-catalyzed hydrolyses. Comparisons with bromelain specificity

Abstract: The specificity of ficin has been investigated using a number of ester and peptide substrates. Three families of esters were used: (i) a series of hippuric acid esters, for which the identity of the values suggests the rate-determining deacylation of a hippuryl-ficin intermediate; (ii) a series of iV-acylglycine p-nitrophenyl esters, for which k0S,t/Km was found to be markedly dependent on the size of the nonpolar acyl group, increasing by a factor of 200 in going from the formyl to the ira/w-cinnamoyl derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1974
1974
2004
2004

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…Several plant cysteine proteases from latex have been reported. Latex of Carica papaya (Glazer and Smith, 1971;Robinson, 1975), Ficus carica (Kramer and Whitaker, 1964;Sgarbieri et al, 1964;Sugiura and Sasaki, 1974), Ficus glabrata (Englund et al, 1968;Jones and Glazer, 1970;Kortt et al, 1974aKortt et al, , 1974bWilliams and Whitaker, 1969), Ficus pumila (Perelló et al, 2000), Carica candamarcensis (Gravina de Moraes et al, 1994), Calotropis procera (Dubey and Jagannadham, 2003), and of Ervatamia coronaria (Kundu et al, 2000) contains distinct cysteine proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Several plant cysteine proteases from latex have been reported. Latex of Carica papaya (Glazer and Smith, 1971;Robinson, 1975), Ficus carica (Kramer and Whitaker, 1964;Sgarbieri et al, 1964;Sugiura and Sasaki, 1974), Ficus glabrata (Englund et al, 1968;Jones and Glazer, 1970;Kortt et al, 1974aKortt et al, , 1974bWilliams and Whitaker, 1969), Ficus pumila (Perelló et al, 2000), Carica candamarcensis (Gravina de Moraes et al, 1994), Calotropis procera (Dubey and Jagannadham, 2003), and of Ervatamia coronaria (Kundu et al, 2000) contains distinct cysteine proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Arg-X and Gln-X bonds may not be the most preferred sites of cleavage by bromelain (10), this cleavage is not inconsistent with the specificity of stem bromelain. Indeed, the enzyme is known to hydrolyze the Arg-Ala bond in the sequence, -Ser-Arg-Arg-Ala-Gln-, of glucagon (11), and the Gln-CyS0 3 H and Gin-Leu bonds in the oxidized insulin A chain (12), and Boc-Leu-Arg-Arg-MCA was shown to be a good substrate for the enzyme in the present study.…”
Section: Isolation Of Bromelain Isoinhibitors and Separation Of The mentioning
confidence: 52%
“…They also showed the ratio of specific activity of bromelain to papain as being 1.1 using casein as substrate, the same as shown in our data. Kortt et al [10] described studies of peptides (bradykinin, insulin, etc.) as substrates for ficin and bromelain and indicated that these enzymes had several differences in their specificities.…”
Section: Resultsmentioning
confidence: 99%